2013
DOI: 10.1155/2013/942916
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Nanoparticle-Induced Oxidative Stress and Toxicity

Abstract: The rapidly emerging field of nanotechnology has offered innovative discoveries in the medical, industrial, and consumer sectors. The unique physicochemical and electrical properties of engineered nanoparticles (NP) make them highly desirable in a variety of applications. However, these novel properties of NP are fraught with concerns for environmental and occupational exposure. Changes in structural and physicochemical properties of NP can lead to changes in biological activities including ROS generation, one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
858
3
14

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,298 publications
(898 citation statements)
references
References 161 publications
(178 reference statements)
23
858
3
14
Order By: Relevance
“…Although mechanisms through which metal/metalloid nanoparticles exert antimicrobial activity are not completely understood, a number of authors claim the production of reactive oxygen species (ROS) as one of the possible modes of action (Manke et al ., 2013; Yan et al ., 2013). In particular, antimicrobial effects of different selenium compounds have been attributed to the formation of free radicals (Tran et al ., 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Although mechanisms through which metal/metalloid nanoparticles exert antimicrobial activity are not completely understood, a number of authors claim the production of reactive oxygen species (ROS) as one of the possible modes of action (Manke et al ., 2013; Yan et al ., 2013). In particular, antimicrobial effects of different selenium compounds have been attributed to the formation of free radicals (Tran et al ., 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative parameters were mainly selected because nanoparticles are known to be associated with the oxidative stress response in many cells or tissue. 53 We measured the NBT (O 2 2 radical measurement) and nitric oxide (NO) of the SCS isolated from both AgNP-MSA-treated and nontreated fibrosarcoma. The results showed that these nanoparticles significantly increased these two parameters in the SCS isolated from fibrosarcoma ( Figure 9), and the anticancer property demonstrated by AgNP can be attributed to this increase in oxidative stress in the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, exposure to the Cr ion also inhibited the gill Na + /K + -ATP activity in Tilapia (Oreochromis niloticus) [35]. Given that the inhibition of the Na + /K + pump by metal ions is well known, the inhibition of CuNP on the Currently, the determinant mechanism of nanoparticlemediated toxicity in organisms is related to the production of oxidative stress and reactive oxygen species (ROS), leading to a series of pathological events such as genotoxicity, inflammation, fibrosis, and carcinogenesis [36]. To protect organisms from oxidative damage, several antioxidant enzymes in organisms are activated to scavenge oxidative stress, including the enzymes of SOD and CAT.…”
Section: Biomarker Responsementioning
confidence: 99%
“…Considering the ions of transition metals (e.g., Cu and Cr) could result in the generation of ROS in organisms via the Haber Weiss and Fenton reactions [38], and the alterations of the antioxidant defense system induced by nanoparticles may be related to the dissolution of free metal ions from the surface of the nanoparticles. In addition, nanoparticles may also stimulate intracellular ROS generation via activation of NADPH-like enzyme system and immune cell after uptake through phagocytosis [36].…”
Section: Biomarker Responsementioning
confidence: 99%